Metode Autoregressive Integrated Moving Average (Arima) dalam Memprediksi Jumlah Penumpang Kereta Api Kota Binjai - Queenty Dhea Haura Br Sitepu; Sutarman Sutarman; Machrani Adi Putri Siregar (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
The importance of land transportation services such as PT. Indonesian Railways are increasing among the public lately, especially in Binjai City. Therefore, this study aims to try to model and forecast the number of passengers of PT. Indonesian Railways in the region. In this study, the Autoregressive Integrated Moving Average (ARIMA) model was used which has proven effective. For research in Binjai City, the ARIMA(1,1,1) model showed good results. The data used in this study includes the number of passengers of PT. Binjai City Railway from January 2022 to December 2022. The forecasting accuracy rate was evaluated using MAPE (Mean Absolute Percentage Error), which reached a value of 4.437%. This figure shows that forecasting has an error rate of less than 10%, so it can be categorized as excellent forecasting. The results of this study provide valuable insights for PT. Binjai City Railway to plan resources and optimize their passenger services. However, further research can still be done to improve forecasting methods and expand the reach of research to other regions.